Endometrial and follicular development following stair-step and traditional protocols in women with polycystic ovary syndrome: An RCT - Sholeh Shahgheibi; Fariba Seyedoshohadaei; Danial Khezri; Solmaz Ghasemi (Shahid Sadoughi University of Medical Sciences, 2021)
Abstract Background: Various strategies have been proposed for polycystic ovary syndrome (PCOS) treatment. Objective: To investigate and compare the number and size of ovarian follicles, endometrial thickness, and ovulation rate by traditional protocol (TP) and stair-step protocol (SSP). Materials and Methods: Sixty infertile PCOS women were allocated into two groups (SSP = 30 and control TP = 30) between May and October 2019 in the Besat Hospital, Sanandaj, Iran. In the SSP group, the infertile women were treated with 50 mg/daily clomiphene citrate (CC) for five days, while the nonresponsive women were prescribed 100 mg daily CC for five days in the same cycle. The maximum dose (150 mg) was administered until ovulation occurred. In the control group, in non-ovulatory cases, the dose was increased in the next cycle. Ultrasound was used to detect ovulation. Results: Endometrial thickness changes with various doses of CC were significantly different in the TP. The comparison of both protocols showed a significant difference in endometrial thickness only at 50 mg CC. The number of follicles in the left ovary was significantly different in both protocols at 150-mg CC. The size of ovarian follicles in the left ovary was significantly different between the two protocols at 100-mg CC. The ovulation rate was significantly different in the SSP at 100- and 150-mg doses of CC. Moreover, 86% of ovulation occurred at 100-mg CC in the SSP, while this rate was 73% in the TP. Conclusion: The most appropriate dose for ovulation in patients with PCOS is 100 mg CC.